Green Waqf Model for Sustainable Waste Management: A Respond to the Economic and Environmental Development - Hasan, Nurul Fatma; Wigati, Sri (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2024)
Purpose: This study proposes a green waqf model for sustainable waste management. Methodology/approach: This research is descriptive and qualitative, using secondary data from books and articles, with data collection through literature review and content analysis to organize and conclude the findings. Results/findings: The proposed green waqf model involves five stages: First, the waqif transfers cash waqf to the waqf institution (nazir). Second, nazir would promote human capital development by using waqf funds to manage training centers equipped with waste management technology. Third, nazirs through training centers would provide skills development training programs to facilitate beneficiaries (mauquf officials) to improve their skills. Fourth, after receiving the necessary skills and training from the nazir, it is expected that the beneficiaries have jobs and boost their productivity output. Finally, monitoring and evaluation should be conducted to ensure continuous improvement. The proposed green waqf model supports economic growth and the Sustainable Development Goals by creating employment opportunities and reducing poverty. As one society benefits, others are motivated to adopt the model, which amplifies its positive impact at the grassroots level. Limitations:  This is literature-based research and has not yet been implemented; therefore, the detailed model needs to be further designed. The model's implementation may be hindered by varying regional infrastructure, the effectiveness of waqf institutions (nazirs), and potential cultural barriers. Contribution: The proposed green waqf model is expected to enhance economic and environmental development.